Language representation in the linguistic landscape of Islamic higher education campuses in East Java - Agwin Degaf; Zainur Rofiq; Raisa Fachira (Universitas Islam Negeri Ar-Raniry, 2026)
Campus signage functions not only as a navigational and informational tool but also as a semiotic medium through which language, identity, and institutional values are communicated and internalized within the quotidian fabric of academic life. Although scholarly discourse has increasingly addressed issues of national integration, global engagement, and the use of religious language in higher education, these linguistic patterns remain insufficiently examined within the context of Indonesian Islamic universities. This study addresses this gap by investigating how language choices on university signage reflect broader ideological, pedagogical, and institutional orientations. Focusing on the linguistic landscapes of three Islamic higher education institutions in East Java, the research maps the display patterns, combinatory strategies, and functional differentiation of Indonesian, English, and Arabic across campus signs. Employing qualitative methods, including the documentation of 147 signs and semi structured interviews with campus stakeholders, the study examines how multilingual signage is interpreted and internalized by its users. The findings indicate a patterned coexistence of the three languages: Indonesian ensures communicative accessibility, English signals global academic aspirations, and Arabic invokes religious and intellectual heritage. These languages do not operate in isolation but interact in layered and symbolic configurations that reflect each institution’s distinct identity and educational mission. The study underscores the need for intentional signage design to reinforce institutional identity, enhance communication effectiveness, and support informal language learning. Future research may extend these findings by examining multilingual signage in other educational contexts or by assessing the impact of sign redesign on user interpretation and engagement.